Types of Antennal Sensilla of Three Pseudacteon Species (Diptera: Phoridae) Females That Parasitize Red Imported Fire Ants (Solenopsis invicta) ( Hymenoptera: Formicidae) - Yong yue Lu (Sociobiology, 2014)
While antenna is the main organ for insect to accept the external chemical signals, the antennal sensilla that are diverse in structure and function form the insect receptors in chemical communication. Since a variety of Pseudacteon species are important natural enemies of the red imported fire ant, Solenopsis invicta Buren (. invicta), to elucidate the types of Pseudacteon sensilla will promote the study and understanding of the selection behavior of Pseudacteon in parasitizing . invicta. This study has used scanning electron microscope (SEM) to observe and investigate the female’s antennal sensilla of three Pseudacteon species, the Pseudacteon (P.) litoralis, P. obtusus, and P. tricuspis, and demonstrated that there are four types of sensilla, the trichoid, basiconic, coeloconic, and chaetic sensilla, on their antennal flagellum. Among them, the former three are common in all three species, with trichoid sensillum as mostly abundant, while the chaetic sensillum exists only in the antennae of P. obtusus. The trichoid sensilla exhibit significant interspecies variations and are further classified into two subtypes based on the presence or absence of protrusions, the surface of which contains different shades of groove-like or irregular punctate structures. The basiconic sensilla resemble short spines with densely porous structures on the surface and are in the length of 7.3-9.8 μm and the width of 1.3-1.6 μm, upright or slightly bent. The coeloconic sensilla are irregularly formed in the middle and base of the flagellum, without surface pores; each coeloconic sensillum has eight finger-like folds in unequal lengths, while the end of the fold resembles a blunt cone. The chaetic sensilla enlarge at the base, possess multiple fold-like structures and fine-tipped ends, and are approximately 5 μm in length.